Representations of Nature of Science in High School Physics Textbooks - Ardwiyanti, D.; Jumadi, J.; Puspitasari, H.; Rahayu, P. (Department of Physics, Faculty of Mathematics and Natural Sciences, 2021)
Nature of science (NOS) is a vital component of scientific literacy that refers to the science's epistemology. Students must possess the NOS conception to address socio-scientific issues using the reasoning and justification patterns like scientists. This qualitative research assessed the representation of NOS quantitatively and qualitatively in the grade XII senior high school physics textbooks. The quantitative representation of NOS was described by the percentage of appearance of each element of NOS, while the delivery approach was used to describe NOS qualitatively. The analysis was conducted on two textbooks focused on electromagnetic radiation, special relativity theory, and quantum phenomena chapters. The NOS framework instrument has been conceptually and empirically valid. The results show that the empirical and scientific theories were addressed with the highest percentage of appearance, while the social and cultural embeddedness of science and scientific methods were poorly addressed. All elements of NOS were represented implicitly. The empirical findings of this study are expected to be able to stimulate the improvement of the representation of NOS in science textbooks in Indonesia.